Marketing of Non-Timber Forest Produce by Large-Sized Adivasi Multipurpose Cooperative Societies in Kodagu District of Karnataka - Basavaraj, G.; Akash, R. G. (Indian Forester, 2025)
The present study was undertaken in Kodagu district of Karnataka state during 2021-22 to study the marketing activities of Large Sized Adivasi Multipurpose Cooperative Society (LAMPS). A sample of 45 members from three LAMPS namely Bhagamandala LAMPS, Thitimathi LAMPS and Basavanhalli LAMPS were selected for the study. The primary mandate of LAMPS is collection and marketing of Non-Timber Forest Products (NTFPs) of members. Among the three LAMPS, Bhagamandala LAMPS procured and sold the highest quantity of NTFPs at 86,105 kg and was the only LAMPS running under profit with an average return on investment ratio of 0.85. Two channels of marketing were observed for marketing of NTFPs. Basavanahalli LAMPS realized a margin of Rs. 65/kg by processing shikakai to powder and the collector’s share in consumer rupee for shikakai was 50 per cent. NTFPs have niche market and Kodagu being a major tourist destination, scope to market NTFPs directly to consumers is very high. Hence, LAMPS should take up value addition activity and sell value added products of NTFPs directly to consumers to enable the collectors realize highest share in consumer rupee.